Effect of Dietary Conjugated Linoleic Acid Supplementation on Early Inflammatory Responses during Cutaneous Wound Healing - Na-Young Park; Giuseppe Valacchi; Yunsook Lim (Mediators of Inflammation)
Inflammatory response is considered the most important period that regulates the entire healing process. Conjugated linoleic acid (CLA), a class of linoleic acid positional and geometric isomers, is well known for its antioxidant and anti-inflammatory properties. We hypothesized that dietary CLA supplementation accelerates cutaneous wound healing by regulating antioxidant and anti-inflammatory functions. To investigate wound closure rates and inflammatory responses, we used a full-thickness excisional wound model after 2-week treatments with control, 0.5%, or 1% CLA-supplemented diet. Mice fed dietary CLA supplementation had reduced levels of oxidative stress and inflammatory markers. Moreover, the wound closure rate was improved significantly in mice fed a 1% CLA-supplemented diet during early stage of wound healing (inflammatory stage). We conclude that dietary CLA supplementation enhances the early stage of cutaneous wound healing as a result of modulating oxidative stress and inflammatory responses.